PELAPORAN TOTAL PENDAPATAN, PAD, DAN PENDAPATAN TRANSFER PEMERINTAH DI ERA PANDEMI COVID-19 (STUDI PADA PEMERINTAH DAERAH DI PROVINSI KALIMANTAN BARAT) - Elsa Sari Yuliana; Murti Puspita Rukmi; V. Ananta (Sekolah Tinggi Pariwisata Mataram, 2021)
The Covid-19 pandemic hit all nations in the world since the end of 2019 until now. One of the efforts to deal with the spread of the Covid-19 virus is to limit human movement in hopes of slowing transmission. With the policy of restriction of movement, it has an impact on the inhibition of economic growth. Economic movements will have an impact on the income of companies and society. This is what underlies the purpose of this study is to analyze the impact of the Covid-19 pandemic on government revenues. This form of research uses qualitative and quantitative methods. The type of data used is secondary data from local government financial statements. This form of research uses qualitative and quantitative methods. The type of data used is secondary data from local government financial statements. Data collection techniques are performed with Documentation, and Library Studies. Analytical techniques with descriptive data analysis methods. This study yielded information that the Covid 19 Pandemic in general has an impact on total local government revenues.